Diseño de la propuesta para la declaratoria del volcán Quilotoa como Geoparque Mundial de la UNESCO. - Cunalata Carrillo, Johana Vanessa (2017)
The present research work has as main objective to design a proposal to declare the Quilotoa area and its enviroments as Unesco World Geopark, located in the Parish of Zumbahua, which belongs to the Pujilí canton and the boundary of the Sigchos canton of the Province of Cotopaxi of the Country Ecuador. The technical guidelines for the postulation were reviewed, that were found on the official website of World Geoparks from United Nations Educational, Scientific and Cultural Organization (UNESCO) so the following guidelines or forms were found that are, The application file indicating in detail the proposed place (Description of the area of Quilotoa and its enviroments), Identification of the area of study (Biodiversity), Geological Heritage, Geoconservation, Economic Activities and Interest as well as, arguments reasoned for the integration to the Global Geoparks Network (RGG) Geological and geographical map showing the location of the future Geopark and a self-assessment form of the proposed Geopark. In order to carry out the design of the proposal, a form was selected regarding the environmental scope that was the application file and with the aid of direct observation, documentary analysis and the field phase, the form was completed. The results obtained from the research were to know the geographic boundary and to identify the characteristics of the biotic, and socioeconomic component of the study area. Keywords: Area, Geological, Geopark, Heritage, UNESCO.